2018
DOI: 10.1111/hepr.13183
|View full text |Cite
|
Sign up to set email alerts
|

Key roles of hepatologists in successful liver transplantation

Abstract: Liver transplantation (LT) has been carried out for acute liver failure, end-stage liver disease, and congenital metabolic disease in more than 7000 cases in Japan. Liver transplantation has been established as a treatment option, and survival rates have improved. In 2016, a new registration/allocation policy and a new scoring system for deceased donor LT were established. The management of perioperative patients and preoperative therapy for liver failure, nutrition, and preventing infection were upgraded. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 92 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…Liver transplantation is an effective treatment for patients with ALF in whom the prognosis appears poor 12 ; however, the waiting time to liver transplantation is considerable as several preparatory steps are required 20 . The present study revealed that registration on the referral system increased the time to onset of HE; therefore benefiting patients who require liver transplantation by allowing them to prepare for intensive care before the development of HE.…”
Section: Discussionmentioning
confidence: 99%
“…Liver transplantation is an effective treatment for patients with ALF in whom the prognosis appears poor 12 ; however, the waiting time to liver transplantation is considerable as several preparatory steps are required 20 . The present study revealed that registration on the referral system increased the time to onset of HE; therefore benefiting patients who require liver transplantation by allowing them to prepare for intensive care before the development of HE.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, although the use of HBIG is associated with several issues, such as a high cost and the emergence of escape mutant, HBIG monotherapy is the dominant form of prophylaxis for HBV recurrence after LT from anti-HBc-positive donors (4,16,23,24). However, recent clinical practice guidelines of AASLD and EASL recommend the administration of antiviral therapy, such as LAM, ETV, tenofovir disoproxil fumarate (TDF), or tenofovir alafenamide (TAF), as these antiviral drugs function as cost-effective treatments due to the low rates of HBV recurrence (< 3%) (5,6,25).…”
Section: Discussionmentioning
confidence: 99%